High-temperature superconductivity at the lanthanum cuprate/lanthanum–strontium nickelate interface. Issue 18 (27th April 2018) - Baiutti, F.; Gregori, G.; Suyolcu, Y. E.; Wang, Y.; Cristiani, G.; Sigle, W.; van Aken, P. A.; Logvenov, G.; Maier, J.
Abstract : Local ionic and electronic redistribution occurs at the lanthanum cuprate/lanthanum nickelate epitaxial contact and gives rise to a high-temperature superconducting layer. Abstract : The utilization of interface effects in epitaxial systems at the nanoscale has emerged as a very powerful approach for engineering functional properties of oxides. Here we present a novel structure fabricated by a state-of-the-art oxide molecular beam epitaxy method and consisting of lanthanum cuprate and strontium (Sr)-doped lanthanum nickelate, in which interfacial high-temperature superconductivity ( T c up to 40 K) occurs at the contact between the two phases. In such a system, we are able to tune the superconducting properties simply by changing the structural parameters. By employing electron spectroscopy and microscopy combined with dedicated conductivity measurements, we show that decoupling occurs between the electronic charge carrier and the cation (Sr) concentration profiles at the interface and that a hole accumulation layer forms, which dictates the resulting superconducting properties. Such effects are rationalized in the light of a generalized space-charge theory for oxide systems that takes account of both ionic and electronic redistribution effects.